INOVASI GURU DALAM PEMBELAJARAN KELAS IV DI SD NEGERI 198/ I PASAR BARU - Intan Dwi Hayu Agustin; Ahmad Hariandi; Muhammad Sholeh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe teacher innovation in fourth grade learning in elementary schools. This research uses a qualitative approach with a phenomenological type of research. This research was carried out at SD Negeri 198/I Pasar Baru in the odd semester of the 2024/2025 academic year. The subject of this research is a class IV teacher. This research data was obtained through observation, interviews and documentation studies (as supporting data). Data validation test using triangulation. The results of this research show that there is teacher innovation in class IV learning at SD Negeri 198/I Pasar Baru. The innovation implemented by the fourth grade teacher is novelty through learning strategies, models, methods and learning media. First, active, creative, effective and fun learning strategy innovation or what could be called the PAKEM learning strategy. This strategy is a method implemented by fourth grade teachers to produce changes in learning that is more active and motivates students. Second, innovation in differentiated learning models with the aim of meeting students' learning needs by adapting to differences in the abilities, interests and ways of learning of class IV students. Third, game method innovation or what is called (gamification method), namely learning that is carried out by accompanying quiz-based game elements for students using an online platform, namely wordwall media. The aim of the game method innovation for class IV teachers is to make learning activities feel more interesting and enjoyable and as a a form of teacher assessment of students to see the extent to which students have understood the lesson material. Fourth, learning media innovation, namely by using interactive media such as learning videos and worldwall applications on online platforms, quiz-based media with many display and image choices so that they can attract students' attention. The results of the research can be concluded that the application of teacher innovation in class IV learning at SD Negeri 198/I Pasar Baru has attempted to create forms of innovation to improve the quality of learning in a better direction.